HUBUNGAN PENDIDIKAN DAN PEKERJAAN IBU HAMIL DENGAN KEIKUTSERTAAN VAKSINASI COVID-19 BOOSTER DI PUSKESMAS KASIHAN 1 BANTUL - Siti Karimah; Fayakun Nur Rohmah; Nuli Nuryanti Zulala (Jurnal Health Sains, 2022)
In Indonesia, cases of COVID-19 among pregnant women make up as much as 10.2% of all confirmed cases. Pregnant women are at risk of being infected with COVID-19 and if infected, their condition will be more severe than other people. One of the efforts to overcome the COVID-19 pandemic is the COVID-19 vaccination. The COVID-19 booster vaccination coverage is 22.52%. Factors that facilitate participation in the COVID-19 booster vaccination for pregnant women are the level of education and occupation. The study aims to determine the correlation between the education level and occupation of pregnant women and the participation of the COVID-19 booster vaccination at Kasihan I Primary Health Center, Bantul. The study employed a quantitative research method in the form of an analytical survey with a cross sectional approach. The population was pregnant women who visited for the first time and recorded on the maternal card of pregnant women in January-May 2022 as many as 302 pregnant women. The research sample was 88 maternal cards of pregnant women taken with purposive sampling. The data analysis in this study was univariate analysis, bivariate analysis with Chi Square, and multivariate analysis with multiple logistic regression test. The results of data analysis showed that the p-value of the education level of pregnant women (0.000) and the p-value of the work of pregnant women (0.000) on the participation of the COVID-19 booster vaccination, meaning that there was a significant correlation between the education level and the occupation of the pregnant women on the participation of the COVID-19 booster vaccination. Based on multiple logistic regression analysis, it was found that the education level of pregnant women provided 4.536 times the opportunity and the occupation of pregnant women gave 0.267 times the opportunity to participate in the COVID-19 booster vaccination. In conclusion, there is a correlation between education and occupation of pregnant women and the participation of the COVID-19 booster vaccination at Kasihan I Primary Health Center, Bantul. Midwives should increase education and support for pregnant women to carry out COVID-19 booster vaccinations.